Promotion of neuroinflammation in select hippocampal regions in a mouse model of perimenopausal Alzheimer’s disease - Marongiu, Roberta; Platholi, Jimcy; Park, Laibaik; Yu, Fangmin; Sommer, Garrett; Woods, Clara; Milner, Teresa A.; Glass, Michael J. (Frontiers in Molecular Biosciences, 2025)
IntroductionAlzheimer’s disease, the most common form of dementia, is characterized by age-dependent amyloid beta (Ab) aggregation and accumulation, neuroinflammation, and cognitive deficits. Significantly, there are prominent sex differences in the risk, onset, progression, and severity of AD, as well as response to therapies, with disease burden disproportionately affecting women. Although menopause onset (i.e., perimenopause) may be a critical transition stage for AD susceptibility in women, the role of early ovarian decline in initial disease pathology, particularly key neuroinflammatory processes, is not well understood.MethodsTo study this, we developed a unique mouse model of perimenopausal AD by combining an accelerated ovarian failure (AOF) model of menopause induced by 4-vinylcyclohexene diepoxide (VCD) with the 5xFAD transgenic AD mouse model. To target early stages of disease progression, 5xFAD females were studied at a young age (∼4 months) and at the beginning stage of ovarian failure analogous to human perimenopause (termed “peri-AOF”), and compared to age-matched males. Assessment of neuropathology was performed by immunohistochemical labeling of Ab as well as markers of astrocyte and microglia activity in the hippocampus, a brain region involved in learning and memory that is deleteriously impacted during AD.ResultsOur results show that genotype, AOF, and sex contributed to AD-like pathology. Aggregation of Ab was heightened in female 5xFAD mice and further increased at peri-AOF, with hippocampal subregion specificity. Further, select increases in glial activation also paralleled Ab pathology in distinct hippocampal subregions. However, cognitive function was not affected by peri-AOF.DiscussionThese findings align with the hypothesis that perimenopause constitutes a period of susceptibility for AD pathogenesis in women.